INTEGRATED SOCIAL SERVICES AT SOCIAL WELFARE CENTER IN LEBAK SILIWANGI COBLONG DISTRICT BANDUNG CITY - Surya Aji, Mohamad Satria; Nelson, Admiral Nelson; Aribowo, Aribowo (Indonesian Journal of Social Work, 2024)
This research aims to describe in depth the integration of social services in the social assistance program carried out by Puskesos Kelurahan Lebak Siliwangi Coblong Kota Bandung with the use of an integrative social services approach, i.e., coordination of services, cooperation, collaboration, and interprofessional. The results of the research obtained show that Puskesos Lebak Siliwangi has integrated social services into the social assistance program with the Social Services Office of Bandung City, the National Amil Zakat Agency (Baznas) of the city of Bandung, and the Rumah Amal Salman. The integration of services in the social assistance program carried out by Puskesos with the relevant parties has been done well, but there are obstacles experienced, such as inaccuracy of information of the recipients of assistance when communicating with the related parties, lack of special appreciation by the service provider, and no brainstorming in the collaboration carried on. All these problems lie on one focus of the problem, which is the lack of joint evaluation of the service process that has been ongoing.